PENGARUH MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE, AND SHARE DAN PREDICT OBSERVE EXPLAIN TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII SMPN 1 GONDANGREJO KARANGANYAR TAHUN AJARAN 2013/2014 - Erfan Budi Santoso; Djumadi Djumadi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
The purpose of this research is to ascertain (1) the influence of SSCS and POE learning model on learning achievement biology of students (2) differences in the biology student learning achievement using learning model SSCS and learning model POE. The research was a quasi experimental research with a design randomized subjects posttest only control group design . The populations in this research were Student in class 8th at SMPN 1 Gondangrejo Karanganyar academic year 2013/2014 . Classes used in the study of 3 randomly selected classes . The first class 8thD applying POE learning model, second class 8thF applying SSCS learning model and the third is a control class 8thE applying conventional learning models specifically models of speech varies and experiment with a simple summary. The data was collected using tests, questionnaires, observation, and documentation. The Analysis using test validity, reliability, difficulty index problem, different power and to test hypotheses about the use of ANOVA and t test with help of SPSS 18. The results showed that : (1) There is the influence of the learning model Search Solve Create and Share (SSCS) and learning model Predict Observe Explain (POE) on learning achievement biology students of SMPN 1 Gondangrejo Karanganyar academic year 2013/2014 both the cognitive, affective , and psychomotor . It can be seen from the average student learning achievement in the experimental class and control classes on the cognitive, affective and psychomotor tests and the results of the ANOVA showed a significance value < 0.05. Further results of the ANOVA Post Hoc test Scheffe there are differences in learning achievement SSCS and POE models on affective and psychomotor domains, whereas the cognitive domain there are differences in learning achievement. The conclusion from the research are: (1) there are significant learning model SSCS and POE to biology students learning achievement, (2) learning model SSCS learning more effectively applied in the class 8th students of SMPN 1 Gondangrejo Karanganyar academic year 2013/2014 than POE and conventional  models it looks from the average value of the results of learning both the cognitive, affective and psychomotor higher grade SSCS. Keywords : SSCS learning models, POE learning models, learning achievement